The Comprehensive Land Use Plan of Iligan City and the Disaster Risk Reduction and Management Framework of the Philippines - ALMAREZ, DAVID; ENRICO PEOAROYA, JOHN; RUBIO, CRISALYN (Universitas Muhammadiyah Yogyakarta, 2015)
This is a descriptive study of the disaster mitigation efforts of Iligan focused on its 1995-2000 and 2013-2022 Comprehensive Land Use Plans (CLUP) and their congruence with the National Disaster Risk Reduction and Management Framework of the Philippines. The key informants engaged are the officials of the City Planning and Development Office who are directly involved in the formulation of the 2013-2022 CLUP. Findings reveal that the 1995-2000 CLUP did not provide for the incorporation of the 4 pillars of Disaster Risk Reduction and anagement (DRRM). Nevertheless, it provided for setbacks in coastal areas, river banks and creeks.However, these setbacks wereviolated by residentialsettlements making them vulnerable to hazards andcontributed to many deaths during the floodingcaused by Tropical Storm Sendong in 2011.Prompted by its disaster experiences and as requiredby the Philippine DRRM Framework, Iligan took stepsin revising its 1995-2000 CLUP by drafting the 2013-2022 CLUP. The 2013-2022 CLUP have incorporated principles of DRRM as prescribed by R.A 10121. These are manifested in new features integrated in the provisions of the plan which include:(1) Analysis matrices with its corresponding strategized programs, projects and activities; (2) Geo-hazard maps assessed by the Mines and Geosciences Bureau (MGB); (3) Vulnerability Assessment Matrix Environment Sector; and (4) Updated and improved version of the Comprehensive Zoning Ordinance of Iligan City. It is highly recommended that Iligan City should strictly implement the provisions of 2013-2022 CLUP in order to increase the city’s resiliency against the occurrence of natural disasters and to achieve sustainable development.KEY WORDS: Comprehensive Land Use Plan, danger zone, naturalhazards, resiliency, vulnerability, zoning ordinance